A new species of the genus Blaberops (Coleoptera: Anthribidae) from east Madagascar, with a key to species - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2014)
A new species, Blaberops korinae Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Zygaenodini), from east Madagascar is described. Colour photographs and a key to Madagascan species of the genus Blaberops are provided. Male and female genitalia of the genus are studied and illustrated for the first time.